2020
DOI: 10.1186/s12910-020-00561-8
|View full text |Cite
|
Sign up to set email alerts
|

“Who is watching the watchdog?”: ethical perspectives of sharing health-related data for precision medicine in Singapore

Abstract: Background We aimed to examine the ethical concerns Singaporeans have about sharing health-data for precision medicine (PM) and identify suggestions for governance strategies. Just as Asian genomes are under-represented in PM, the views of Asian populations about the risks and benefits of data sharing are under-represented in prior attitudinal research. Methods We conducted seven focus groups with 62 participants in Singapore from May to July 2019. They were conducted in three languages (English, Mandarin an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Our findings demonstrate that Singaporeans were significantly less willing to share data with private insurance than with pharmaceutical companies. This finding is consistent with prior qualitative studies in Singapore that have reported an openness to sharing with pharmaceutical companies for research that can generate public benefit, but not private insurers [27]. It is also consistent with the relative trust of users in our survey, which measured significantly lower levels for private insurers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings demonstrate that Singaporeans were significantly less willing to share data with private insurance than with pharmaceutical companies. This finding is consistent with prior qualitative studies in Singapore that have reported an openness to sharing with pharmaceutical companies for research that can generate public benefit, but not private insurers [27]. It is also consistent with the relative trust of users in our survey, which measured significantly lower levels for private insurers.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study in the Republic of Korea also found a strong preference for PM research to be carried out by government agencies [54] suggesting that East and Southeast Asian 'developmental states' [55] may exhibit higher trust in governments, including with respect to data research, than countries in Europe and North America. Singapore, in general, has relatively high levels of trust in government [56,57] and prior qualitative research in Singapore has also reported high trust in government agencies to manage and use PM data [27]. Furthermore, it is possible that Singapore's management of the SARS-CoV-2 pandemic, widely recognized as effective and competent [58,59], boosted Singaporeans' trust in government at the time when our survey was conducted; indeed, according to the Elderman Trust Barometer survey [60], 2020 saw exceptionally high levels of trust in governments globally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, younger people and females are less likely to participate in consenting to data reuse 55 . Fears of loss of privacy or confidentiality breach, commercialisation of data, misuse and abuse are equally concerning [56][57][58][59] . These concerns are also driven by insufficient public engagement and low public awareness of research governance, participant protection and risk minimisation measures 54 .…”
Section: Perceived Challenges Risks and Considerations For Data Sharingmentioning
confidence: 99%